Water balance for gaged watersheds in the Central Sierra Nevada, California and Nevada, United States - Roche, James W.; Wilson, Kristen N.; Ma, Qin; Bales, Roger C. (Frontiers in Forests and Global Change, 2022)
Watershed managers require accurate, high-spatial-resolution evapotranspiration (ET) data to evaluate forest susceptibility to drought or catastrophic wildfire, and to determine opportunities for enhancing streamflow or forest resilience under climate warming. We evaluate an easily calculated product by using annual gridded precipitation (P) and measured discharge (Q), together with a gridded ET product developed from ET and P measured at flux towers plus Landsat NDVI (normalized difference vegetation index) to evaluate uncertainties in water balances across 52 watersheds with stream-gauge measurements in the Central Sierra Nevada. Watershed areas ranged from 5 to 4823 km2, and the study-area elevation range was 52–3302 m. Study-area P, ET, and Q averaged 1263, 634, and 573 mm yr–1 respectively, with precipitation at higher elevations up to five times that at lower elevations. We assessed uncertainty in water-balance components by applying a multiplier to P or Q values across the period of record for each watershed to align annual P-ET and Q values, resulting in average P-ET-Q = 0. Most year-to-year values of annual change in storage (ΔS), calculated as P-ET-Q for watersheds with well-constrained water balances, were within about + 300 mm. Across the study area we found that for each of 37 watersheds, applying a constant multiplier to either annual P or Q resulted in well-constrained water balances (average annual P-ET-Q = 0). Multiplicative adjustment of ET values for each watershed did not improve average water balances over the period of record, and would result in inconsistent values across adjacent and nested watersheds. For a given watershed, ET was relatively constant from year to year, with precipitation variability driving both interannual and spatial variability in runoff. These findings highlight the importance of evapotranspiration as a central metric of water-balance change and variability, and the strength of using high-confidence spatial- evapotranspiration estimates to diagnose uncertainties in annual water balances, and the components contributing to those uncertainties.